Presentation and Management of Soft-Tissue Foreign Bodies in a Teaching Hospital of Western Nepal - Joshi, Ruban Raj; Dwivedi, Rajeev (Journal of Lumbini Medical College, 2016)
Introduction: Accidental penetrating injuries with foreign bodies are a common presentation in hospital's emergency rooms. If missed, these bodies can remain dormant or result in a wide range of complications. This study evaluated the characteristics of patients, presentation and management who suffered foreign body embedded in soft tissue at a teaching hospital of Western Nepal. Methods: The study was conducted at Department of Orthopaedics, Lumbini Medical College Teaching Hospital from September 2013 to August 2015. All cases confirmed to have a foreign body in soft tissue were enrolled. Surgical exploration with removal of foreign body was carried in operating room under tourniquet control. The patient demographics, cause of injury, nature of foreign body, occupation of the patient, diagnostic yield of radioimaging, procedures undertaken for retrieval of foreign body, and complications were recorded. All patients were followed-up up to five months. Results: Total 28 patients, nine (32.1%) males and 19 females (67.9%) were observed. The mean age was 35.6 yr (SD=11.1). Housewives (n=14, 50%) were the common sufferers. Most of our patients (n=17, 60.7%) presented two weeks after injury. Accidental prick while cutting grass or tree was the common mode (n=13, 46.3%) of injury and among foreign bodies, wooden or vegetative were the commonest (n=19, 67.9%) observed. Among the extremities, hand (n=10, 35.7%) and foot (n=5, 17.9%) were commonly affected. All patients had successful surgical exploration and retrieval of the foreign bodies under anesthesia and tourniquet control in operating room. Image intensifier was employed in seven cases to locate the foreign bodies per-operatively. Wound infection developed in 14.2% (n=4) of patients, all of whom were managed successfully with oral antibiotics. None of the patients required re-hospitalization. All patients were fine at final five months follow up. Conclusion: Managing foreign body embedded in the soft tissue are challenging. Surgical exploration under tourniquet control suffice a definitive management. At times, image intensifier is required to locate the foreign body. DOI: https://doi.org/10.22502/jlmc.v3i2.73 J. Lumbini. Med. Coll. Vol 3, No 2, July-Dec 2015, page: 50-54